2021
DOI: 10.1101/2021.08.09.21261754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of health care services during the Covid-19 pandemic in Ethiopia: Evidence from a health facility survey

Abstract: Introduction: In recent years Ethiopia has made enormous strides in enhancing access to health care, especially, maternal and child health care (MCH). With the onset and spread of Covid-19, the attention of the health care system has pivoted to handling the disease, potentially at the cost of other health care needs. This paper explores whether this shift has come at the cost of non Covid related health care, especially the use of MCH services. Methods: Graphs, descriptive statistics and paired t-tests of sig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Out of twenty-one selected studies; thirteen studies were quantitative cross-sectional studies, five were mixed (quantitative and qualitative) studies, two were pre-post studies, and one was a qualitative study. Sixteen studies were published [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] while the other five studies were unpublished [55][56][57][58][59]. Seven studies were conducted in Addis Ababa administrative city [39,42,43,46,47,55,58], three studies were conducted in Southern Nations Nationalities and People (SNNPR) [44,51,59], four studies were from Amhara region [40,45,49,57], four studies were nationwide surveys [48,50,52,56], one study was in Oromia region [53], one study was from Tigray region [54], and one study was conducted in Somali region [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of twenty-one selected studies; thirteen studies were quantitative cross-sectional studies, five were mixed (quantitative and qualitative) studies, two were pre-post studies, and one was a qualitative study. Sixteen studies were published [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] while the other five studies were unpublished [55][56][57][58][59]. Seven studies were conducted in Addis Ababa administrative city [39,42,43,46,47,55,58], three studies were conducted in Southern Nations Nationalities and People (SNNPR) [44,51,59], four studies were from Amhara region [40,45,49,57], four studies were nationwide surveys [48,50,52,56], one study was in Oromia region [53], one study was from Tigray region [54], and one study was conducted in Somali region [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sixteen studies were published [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] while the other five studies were unpublished [55][56][57][58][59]. Seven studies were conducted in Addis Ababa administrative city [39,42,43,46,47,55,58], three studies were conducted in Southern Nations Nationalities and People (SNNPR) [44,51,59], four studies were from Amhara region [40,45,49,57], four studies were nationwide surveys [48,50,52,56], one study was in Oromia region [53], one study was from Tigray region [54], and one study was conducted in Somali region [41]. Eleven studies reported quantitative findings on the reduction of antenatal care, ten studies reported the reduction of family planning, six studies reported a decrease in facility delivery, four studies reported the reduction of abortion care, and three studies reported a reduction in postnatal care services.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…At the same time, the MOH ensured the continuation of essential services, such as reproductive, maternal, neonatal, child, and adolescent health services, and the management of major communicable and noncommunicable diseases, surgical care, and emergency and critical care [12]. Despite several studies conducted on the impact of COVID 19 on maternal health services in different regions of the country [13][14][15][16][17][18][19][20], there is a lack of evidence that can recapitulate the extent of impact as a nation and which essential maternal health service is most affected. Thus this systematic review aims to summarize the extent of disruption of essential maternal health services and identify the most significantly affected service in the era of the COVID pandemic in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%